METHODOLOGY OF FORMING PROFESSIONAL COMPETENCES IN PRIMARY CLASS TECHNOLOGY LESSONS (Academicia Globe: Inderscience Research, 2024)
In this article, the content of the concept of competence, modern methods and the issue of formation of professional competences of students in elementary school technology classes are explained.